Structural Characterization of the Extracellular Domain of CASPR2 and Insights into Its Association with the Novel Ligand Contactin1 - Rubio-Marrero, Eva N; Vincelli, Gabriele; Jeffries, Cy M; Shaikh, Tanvir R; Pakos, Irene S; Ranaivoson, Fanomezana M; von Daake, Sventja; Demeler, Borries; De Jaco, Antonella; Perkins, Guy; Ellisman, Mark H; Trewhella, Jill; et al. (The Journal of biological chemistry, 2016)
Contactin-associated protein-like 2 (CNTNAP2) encodes for CASPR2, a multidomain single transmembrane protein belonging to the neurexin superfamily that has been implicated in a broad range of human phenotypes including autism and language impairment. Using a combination of biophysical techniques, including small angle x-ray scattering, single particle electron microscopy, analytical ultracentrifugation, and bio-layer interferometry, we present novel structural and functional data that relate the architecture of the extracellular domain of CASPR2 to a previously unknown ligand, Contactin1 (CNTN1). Structurally, CASPR2 is highly glycosylated and has an overall compact architecture. Functionally, we show that CASPR2 associates with micromolar affinity with CNTN1 but, under the same conditions, it does not interact with any of the other members of the contactin family. Moreover, by using dissociated hippocampal neurons we show that microbeads loaded with CASPR2, but not with a deletion mutant, co-localize with transfected CNTN1, suggesting that CNTN1 is an endogenous ligand for CASPR2. These data provide novel insights into the structure and function of CASPR2, suggesting a complex role of CASPR2 in the nervous system.
Keywords: analytical ultracentrifugation; Animals; hipokampus; kontaktin 1; Protein Structure, Tertiary; Scattering, Small Angle; HEK293 Cells; terciární struktura proteinů; Contactin 1; lidé; maloúhlový rozptyl; protein structure; membránové proteiny; Protein Interaction Maps; kultivované buňky; HEK293 buňky; proteiny nervové tkáně; mapy interakcí proteinů; Models, Molecular; Cells, Cultured; X-Ray Diffraction; molekulární modely; Nerve Tissue Proteins; small-angle x-ray scattering (SAXS); difrakce rentgenového záření; ligand-binding protein; molecular cell biology; Membrane Proteins; Hippocampus; zvířata; Mice, Inbred C57BL; myši inbrední C57BL; Humans